Experimental Staphylococcus aureus Mastitis Infection Model by Teat Dipping in Bacterial Culture Suspension in Dairy Cows - Oudessa Kerro Dego; Paulina A. Pacha; Barbara E. Gillespie; Gina M. Pighetti (Animals, 2020)
Mastitis is inflammation of mammary glands usually caused by bacteria such as Staphylococcus aureus. Dairy cows are susceptible to mastitis during early dry and transition periods. Effective vaccine is needed during these periods. One of the limitations to develop an effective vaccine against S. aureus is the absence of good infection model. Intramammary infusion (IMIF) with S. aureus has been used as an infection model to test vaccine efficacy. IMIF is reliable in causing mastitis, but it bypasses physical barriers, non-specific natural defenses, and immunity in the teat canal. IMIF also transfers a large number of bacteria into the intramammary area at once. The objective of this study was to develop S. aureus IMIF model that mimics natural infection. Eight Holstein dairy cows were randomly divided into two groups of experimental (n = 5) and control (n = 3) cows. All teats of experimental cows were dipped in S. aureus culture suspension, whereas that of control cows were dipped in phosphate-buffered saline. Results showed that four of five cows were infected with challenge strain by day 3 of the challenge. The remaining cow was infected with Staphylococcus chromogenes. In conclusion, an experimental S. aureus intramammary infection can be induced by teat dipping into bacterial suspension.